2008
DOI: 10.2319/091707-444.1
|View full text |Cite
|
Sign up to set email alerts
|

Condition-Specific Impacts on Quality of Life Attributed to Malocclusion by Adolescents with Normal Occlusion and Class I, II and III Malocclusion

Abstract: Objective: To compare the prevalence, intensity, and extent of condition-specific oral impacts on quality of life attributed to malocclusion by Brazilian adolescents with normal occlusion and those with Angle Class I, II, and III malocclusion. Materials and Methods: Four groups of 55 adolescents were configured such that each group represented normal occlusion, as well as Angle Class I, II, and III malocclusion. No radiographs were taken. Adolescents aged 15 to 16 years were selected from those attending all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 16 publications
1
32
0
5
Order By: Relevance
“…7 Indeed, adolescents with malocclusion can experience poor masticatory efficiency and ability. 8 Parents/caregivers are often the main decision makers regarding their children's health, and their perceptions have a major influence on treatment choices. 9 Therefore, even when adolescents are able to provide self-reports, parents/caregivers' proxy reports should be obtained to provide additional and complementary information about the impact of different oral outcomes on adolescents' OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…7 Indeed, adolescents with malocclusion can experience poor masticatory efficiency and ability. 8 Parents/caregivers are often the main decision makers regarding their children's health, and their perceptions have a major influence on treatment choices. 9 Therefore, even when adolescents are able to provide self-reports, parents/caregivers' proxy reports should be obtained to provide additional and complementary information about the impact of different oral outcomes on adolescents' OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Through a logistic regression analysis it was possible to calculate that people with malocclusion class II and III are more likely to have a negative impact on quality of life than individuals with class I. This was probably due to the fact that individuals with most severe malocclusions are more likely to suffer physical and psychosocial problems [38] such as dental traumas [39] and bullying [40] which directly interfere with the quality of life. A metaanalysis on the social effects of bullying associated with malocclusion suggested that victims suffer from psychological problems [41], and the present study shows that physical pain and psychological discomfort, followed by psychological disability (Figure 03), were the items that caused the greatest negative impact on quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Unmet dental needs due to dental caries have negative impact on the daily activities of children with functional domain mostly affected 13 . Oral conditions such as malocclusion have also been associated with impacts on the quality of life of affected individuals 14 and affecting the psychological and social domains most 15,16 . This is especially important among adolescents who are undergoing physical, psychological, emotional and social life changes, and are under various forms of pressure to be accepted by their peers, while maintaining their 'status' in the home front 17 .…”
Section: Introductionmentioning
confidence: 99%